Characterization of Four Hazelnut (Corylus avellana) Populations by Some of their Biological and Biochemical Traits - James Gacheru Wanjiku; Heike Bohne (Research Advances and Challenges in Agricultural Sciences Vol. 9, 2024)
The aim of characterizing these four populations was to determine whether there were any variations (local adaptation) among the four Corylus avellana L. (Hazelnut) populations. Variations considered included; leaf phenology (sprouting and setting), growth, mineral nutrient acquisition (N, P, K) and biochemical composition (glucose, fructose, sucrose, starch and proline). These were evaluated after co-cultivation in a common-container area. The cuttings were sourced from four distinct populations, rooted and cultivated under similar conditions for four years. Phenologies were scored in spring (March to April) and in autumn (October to November) for bud sprouting and bud set respectively. The plants were sampled twice per year in spring (April) and in autumn for nutrient and biochemical analyses. There were no significant differences in phenology and growth among populations. The phenology was related to the annual temperature and varied with the years. For most nutrient and biochemical parameters, there were no significant differences among the populations. Finally, the study highlighted the fact that both phenology timing and growth rate were consistent from year to year. The results demonstrated that despite the reported genetic differences and distance among the populations in their natural habitats, there were no local differentiations upon local co-cultivation. This demonstrated the great adaptive plasticity of hazelnuts to different climatic conditions. These adaptive capacities acting among the population could allow populations to cope with climate change and transfer, as in assisted migration, within the range tested.